Judicial Immunity from Charter Review: Myth or Reality? - Otis, Ghislain (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1989)
In the first part of this article, the author argues that the Supreme Court's exclusion of the judiciary from the ambit of section 32(1) of the Canadian Charter of Rights and Freedoms does not create an immunity from Charter review in favour of courts and judges. He identifies two broad categories of cases where judicial action is indeed subject to Charter scrutiny. In these cases the Charter applies because a basis for review can be found independently of section 32(1) and because there is no risk of a direct intrusion of Charter dictates into the private sphere. In the second part of the paper, the appropriate remedial response to judicial breaches of Charter guarantees is investigated. It is shown that the statutory and common law rules restricting judicial liability cannot dictate when a monetary award is "appropriate and just" within the terms of section 24(1) of the Charter. Personal immunity from constitutional suits, however, appears to be required as an aspect of the constitutional principle of judicial independence.